Telecontrolling Catfish Breeding Ponds Based on Wireless Sensor Networks with Solar Energy Implementation (Case Study: Catfish Breeding Berkah Maju Bersama Malang) - Fahmi, Yusuf Iqbal; Mustafa, Lis Diana; Junus, Mochammad (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Catfish Breeding Farmer Group Berkah Maju Bersama is a farmer group that focuses on catfish breeding activities. This group has an address in Plaosan Village, Wonosari District, Malang Regency. Challenges in maintaining optimal pond conditions and effective monitoring are often faced by these farmer groups. In an attempt to address this problem, the study proposes a telecontrol system of catfish breeding ponds using wireless sensors with the implementation of solar energy. This study aims to create and design a catfish breeding pond telecontrol system by implementing solar energy. This research uses ESP32 as microcontroller, temperature sensor (DS18B20), pH sensor Module 4502C, LoRa type E220-400T30D. The results of the study in the form of temperature sensors have a percentage of sensor reading accuracy of 99.99%, pH sensors have a percentage of sensor reading accuracy of 99.99%. The maximum distance of data transmission by LoRa is 1213 meters, charging by solar panels for 7 hours 4.375 Ah(31.25% of the total battery capacity), and battery discharge is 0.356 Ah(abterai lasts for 98 hours). The calibration of the pH sensor module 4502C reads the pH value according to the reading of the pH meter analyzer. Overall, the system can run well. The lights and solenoid valve can be active with two modes, namely manual mode and auto mode contained in website features.